Review of the Southeast Asian millipede genus Enghoffosoma Golovatch, 1993 (Diplopoda, Polydesmida, Paradoxosomatidae), with descriptions of new species - Likhitrakarn, Natdanai; Golovatch, Sergei I.; Panha, Somsak (Zootaxa, 2014)
The Southeast Asian millipede genus Enghoffosoma ranges from southern China in the north, western Myanmar in the west, and central Thailand and southern Laos in the south and east. It currently contains seven species, including five new ones, described in this paper: E. zebra sp. n., E. lanceolatum sp. n., E. anchoriforme sp. n., E. funda sp. n. and E. bispinum sp. n. The genus is rediagnosed, a key to all known species is given, and their distributions are mapped.